Low Levels of Vitamin D correlate with Hemoglobin A1c and Interleukin-10 Levels in Pediatric Type 1 Diabetes Mellitus Patients - Desy Wulandari; Haryudi A. Cahyono; Edi Widjajanto; Anik Puryatni (Journal of Tropical Life Science, 2014)
Vitamin D is reported to affect immune system and prevent autoimmunity. Some studies show that low vitamin D levels in patients with type 1 diabetes are associated with glycemic control and inflammatory status. The study was cross sectional design with subjects T1DM patients aged 1-18 years, and healthy subjects with similar age. Plasma levels of vitamin D (25(OH)D3) was measured using ELISA. Glycemic control measured by hemoglobin A1c (HbA1c). Inflammatory status measured by examination of IL-10 using ELISA method. Comparison of vitamin D levels, HbA1c levels and IL-10 levels were analyzed by independent samples t-test. The relationship between vitamin D levels, HbA1c, and IL-10 were analyzed by Pearson's correlation. Our subjects were 20 T1DM patients and 20 healthy controls. Our study showed that vitamin D (25(OH)D3) levels was significantly lower than in healthy controls (20.82±5.53 ng/ml vs 33.14±2.17 ng/ml; p=0.000), HbA1c levels was significantly higher than in healthy controls (10.08±5.02% vs 5.02±0.18%; p=0.000), IL-10 levels was significantly lower than in healthy controls (16.50±4.57 ng/ml vs 73.52±7.11 ng/ml; p=0.000). Vitamin D levels were correlated with HbA1c (p= 0.000; r= -0.871), correlated with IL-10 (p= 0.000; r= 0.853). HbA1c levels were correlated with IL-10 levels (p= 0.000; r= -0.878). Low vitamin D levels are common in T1DM patients. There were significant differences in vitamin D levels, IL-10, and HbA1c among T1DM patients compared to normal subjects. Vitamin D levels were associated with HbA1c levels and IL-10 levels in T1DM.